2009
DOI: 10.1080/09720073.2009.11891108
|View full text |Cite
|
Sign up to set email alerts
|

Menarcheal and Menopausal Age Distribution among the Kshatriya Women of North Coastal Andhra Pradesh

Abstract: Menarche and menopause demarcate the limits of potential reproductive life span in the female. A number of studies have conducted on this aspect in different endogamous population of Andhra Pradesh at different time's .For the present work the urban and rural areas of Kshatriya women have been taken to study and this population has not studied previously on this aspect. In the study population it has been observed that, the early menarche in urban area while late menarche more in rural area. The difference of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2014
2014
2014
2014

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 5 publications
(5 reference statements)
1
1
0
Order By: Relevance
“…Further, the percentage of rural women attaining early menopause, that is, before the age of 40 years, was higher in rural areas (8.9 per cent). These findings are very similar to the findings of a study done in Andhra Pradesh (see Priya et al 2009). D. Lawlor et al (2004) have argued that, to understand the early age of menopause of women, it is necessary to study the effect of the socioeconomic position of women across the life course and age at menopause.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Further, the percentage of rural women attaining early menopause, that is, before the age of 40 years, was higher in rural areas (8.9 per cent). These findings are very similar to the findings of a study done in Andhra Pradesh (see Priya et al 2009). D. Lawlor et al (2004) have argued that, to understand the early age of menopause of women, it is necessary to study the effect of the socioeconomic position of women across the life course and age at menopause.…”
Section: Discussionsupporting
confidence: 86%
“…Some studies report early onset of menopause among rural women (Syamala and Sivakami 2005; Sagdeo and Arora 2011), but others report later onset (Dasgupta and Ray 2009). One study undertaken in coastal Andhra Pradesh (Priya et al 2009) concluded that the difference in mean menopausal age between rural and urban areas was not significant.…”
Section: Earlier Research and Research Gapmentioning
confidence: 99%